2024
DOI: 10.1161/circresaha.123.323617
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Exposure and Cardiovascular Disease

Ziwei Pan,
Tingyu Gong,
Ping Liang

Abstract: Heavy metals are harmful environmental pollutants that have attracted widespread attention due to their health hazards to human cardiovascular disease. Heavy metals, including lead, cadmium, mercury, arsenic, and chromium, are found in various sources such as air, water, soil, food, and industrial products. Recent research strongly suggests a connection between cardiovascular disease and exposure to toxic heavy metals. Epidemiological, basic, and clinical studies have revealed that heavy metals can promote the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 201 publications
(305 reference statements)
0
2
0
Order By: Relevance
“…The results showed that exogenous harmful substance exposure was a risk factor for COPD and the co-morbidity of COPD and hypertension, but the association between hypertension alone was not statistically significant. Previous studies have shown an association between heavy metal exposure and hypertension development ( 14 ), but essentially no studies have reported an association between exposures to substances such as inorganic mineral dust and agricultural and livestock by-products and hypertension. The results demonstrate that exposure to exogenous harmful substances contributes to the development of COPD and that the exposure increases the risk of hypertension co-morbidity in those who already have COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that exogenous harmful substance exposure was a risk factor for COPD and the co-morbidity of COPD and hypertension, but the association between hypertension alone was not statistically significant. Previous studies have shown an association between heavy metal exposure and hypertension development ( 14 ), but essentially no studies have reported an association between exposures to substances such as inorganic mineral dust and agricultural and livestock by-products and hypertension. The results demonstrate that exposure to exogenous harmful substances contributes to the development of COPD and that the exposure increases the risk of hypertension co-morbidity in those who already have COPD.…”
Section: Discussionmentioning
confidence: 99%
“…A study based on NHANES data found that co-exposure to polycyclic aromatic hydrocarbons (PAHs) was associated with COPD (OR = 1.44, 95% CI: 1.09–1.90) ( 13 ). Meanwhile, epidemiological and clinical studies have shown that heavy metals can promote the production of reactive oxygen species and induce inflammation, leading to an increased risk of hypertension, cardiac arrhythmias, and atherosclerosis ( 14 ). The effects of exogenous harmful substance exposure were diverse and complex ( 15 ), with many populations found to have been exposed to exogenous harmful substances from industries such as the chemical or smelting, textile, and animal husbandry ( 16 ).…”
Section: Introductionmentioning
confidence: 99%